2023
DOI: 10.3390/jcm12227186
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Endovascular and Open Surgical Treatment for Ruptured Abdominal Aortic Aneurysm in Terms of Safety and Efficacy on the Basis of a Single-Center 30-Year Experience

Mansur Duran,
Amir Arnautovic,
Cem Kilic
et al.

Abstract: Objective: Ruptured abdominal aortic aneurysm (rAAA) is a critical condition with a high mortality rate. Over the years, endovascular aortic repair (EVAR) has evolved as a viable treatment option in addition to open repair (OR). The primary objective of this study was to compare the safety and efficacy of EVAR and OR for the treatment of rAAA based on a comprehensive analysis of our single-centre 30-year experience. Methods: Patients treated for rAAA at the Department of Vascular and Endovascular Surgery, Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…These encouraging and pioneering results should be confirmed by larger studies that compare hypnosis and LA to sedation and LA. Indeed, minimally invasive and percutaneous endovascular procedures, such as EVAR, minimize tissue injury and the need for GA [14]. No study has reported results on hypnosis compared to GA in endovascular aortic surgery, but several studies have shown a benefit of conscious sedation and LA in EVAR [1,[3][4][5][6]15,16].…”
Section: Discussionmentioning
confidence: 99%
“…These encouraging and pioneering results should be confirmed by larger studies that compare hypnosis and LA to sedation and LA. Indeed, minimally invasive and percutaneous endovascular procedures, such as EVAR, minimize tissue injury and the need for GA [14]. No study has reported results on hypnosis compared to GA in endovascular aortic surgery, but several studies have shown a benefit of conscious sedation and LA in EVAR [1,[3][4][5][6]15,16].…”
Section: Discussionmentioning
confidence: 99%